Atmospheric pollution and its implications with special reference to the Kuils River industrial area - Samson, J. J.(Jacqueline Joy) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. in Town and Regional Planning) -- University of Stellenbosch, 1994.